2018
DOI: 10.29333/ejmste/83677
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection Influences the Reactions of Children to Potentially Dangerous Animals

Abstract: Certain animals have represented a danger to humans in terms of a predation and pathogen threat over our evolutionary history. It is therefore adaptive for people to respond to a potential threat faster than to harmless events. Using simple choice tasks, the reaction time of children to predators, disease carriers and aposematically coloured animals were investigated. Children reacted the fastest to predators, followed by disease carriers and finally aposematically coloured animals. Furthermore, children manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…In line with this view, a number of studies have suggested that our perceptualattentional processes were shaped by predation (Isbell, 2009). Likewise, it has been found that adults detect dangerous animals-like snakes or lions-more quickly than non-dangerous animals (LoBue & DeLoache, 2008;Prokop, 2018;Yorzinski et al, 2014;Yorzinski, Tovar, & Coss, 2018). For instance, in a study conducted by LoBue and DeLoache (2008), preschool children and adults were asked to find and then touch "threatening" target pictures on a screen (e.g., snakes) among matrices of "nonthreatening" distractors (e.g., mushrooms) or to do the reverse.…”
mentioning
confidence: 84%
“…In line with this view, a number of studies have suggested that our perceptualattentional processes were shaped by predation (Isbell, 2009). Likewise, it has been found that adults detect dangerous animals-like snakes or lions-more quickly than non-dangerous animals (LoBue & DeLoache, 2008;Prokop, 2018;Yorzinski et al, 2014;Yorzinski, Tovar, & Coss, 2018). For instance, in a study conducted by LoBue and DeLoache (2008), preschool children and adults were asked to find and then touch "threatening" target pictures on a screen (e.g., snakes) among matrices of "nonthreatening" distractors (e.g., mushrooms) or to do the reverse.…”
mentioning
confidence: 84%
“…To manipulate the pathogenicity of animal targets, we used photographs of animal vectors of zoonotic infectious diseases. To determine which animals to use, we utilized the World Health Organization's list of vector-borne diseases (WHO, 2020) as well as the list of disease-relevant animal species presented in the related studies (e.g., Prokop et al, 2010a;Prokop, 2018). Thus, 8 disease vectors and 8 disease-neutral animals have been identi ed, with both categories consisting of 5 invertebrate and 3 vertebrate species.…”
Section: Methodsmentioning
confidence: 99%
“…Both large phytophagous mammals, as well as large carnivorous mammals, cause human mortality (Bombieri et al, 2019; Røskaft et al, 2003; Thant et al, 2022; Treves & Naughton‐Treves, 1999). Human attention is significantly captured by the presence of large animals (Prokop, 2018; Ward et al, 1998; Yorzinski et al, 2014; Yorzinski & Coss, 2020). In addition, according to the stereotype content model (Fiske et al, 2002), the high intelligence (positive trait) and aggression (negative trait) of large predators are associated with mixed stereotypes of fear and admiration (Sevillano & Fiske, 2016).…”
Section: Introductionmentioning
confidence: 99%